Kupiah Riman Ornament Motif as a Cultural Representation of the Acehnese Community - Ismawan Ismawan; Tri Supadmi; Tengku Hartati; Lindawati Lindawati (Proceedings of AICS - Social Sciences, 2021)
The research entitled "Kupiah Riman Ornament Motifs as a Cultural Representation of the Acehnese Community '' aims to determine the Acehnese decorative motifs on Kupiah Riman as a cultural representation of the Acehnese people. Kupiah Riman is one type of handicrafts in the province of Aceh which serves to cover the head. Kupiah Riman is made from palm fiber. The manufacture is done manually with weaving and embroidery techniques, but this research focused on decorative motifs that are consistently applied to the kupiah. The approach in this research was qualitative with a descriptive type of research. The research data collection was done by means of observation, interview, and documentation. The data analysis was carried out by means of data reduction, data display, and conclusion drawing/verification. The sources of data in this study were Kurniadi, the owner of Kupiah riman production as well as craftsmen, Badriyah, Nurhammah, Yunidar, Aisyah, and Nurhayati as Kupiah riman craftsmen, and the object of this research was the composition of motifs on Kupiah Riman. The results showed that the motifs applied consistently to Kupiah riman included the rainbow lines (Gareh peulangi), bamboo shoots (Pucok reubong), rectangular flowers (Bungong petak), Aceh Door (Pinto Aceh), headland flower (Bungong keupula), Cloud flower (Bungong Awan). These motifs are a description of natural and man-made phenomena that are used in people's lives to meet basic (primary) or additional (secondary) needs. This natural phenomenon is always present and is considered to have a role in the cultural life of the Acehnese people. These phenomena are abstracted into decorative forms using stylization and deformation techniques and even distortion and applied to Kupiah Riman. Therefore, it is clear that the motifs applied to the handicraft products of “Kupiah Riman'' represent the culture of the Acehnese people.Keywords: Crafts, culture, society, Kupiah Riman.